2020
DOI: 10.1038/s41598-020-62317-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species scavenging mechanisms associated with polyethylene glycol mediated osmotic stress tolerance in Chinese potato

Abstract: Influence of polyethylene glycol (PEG) mediated osmotic stress on reactive oxygen species (ROS) scavenging machinery of Chinese potato (Solenostemon rotundifolius (Poir.) J. K. Morton) was investigated. Five genotypes of Chinese potato were raised in Murashige and Skoog (MS) basal medium containing 6-benzylaminopurine (BAP, 1 mg L-1) along with various concentrations of PEG-6000 mediated stress conditions (0,-0.2 and-0.5 MPa) and evaluated for osmotic stress tolerance in vitro. The medium containing PEG-6000 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The higher Na + concentration in the plant leads to inhibit the uptake of K + ions, which is one of the essential mineral elements for growth and development [73]. In response to the imbalance of ionic concentration in the cell, it undergoes salinity stress, leading to ROS production, such as singlet oxygen, hydrogen peroxide, and superoxide radicals, which further interrupt the vital cellular functions of the potato plant [21,74,75]. The ionic homeostasis is maintained under salt stress by adjusting K + and Na + ions by their acquisition and distribution in plants.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…The higher Na + concentration in the plant leads to inhibit the uptake of K + ions, which is one of the essential mineral elements for growth and development [73]. In response to the imbalance of ionic concentration in the cell, it undergoes salinity stress, leading to ROS production, such as singlet oxygen, hydrogen peroxide, and superoxide radicals, which further interrupt the vital cellular functions of the potato plant [21,74,75]. The ionic homeostasis is maintained under salt stress by adjusting K + and Na + ions by their acquisition and distribution in plants.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…Previous studies documented the role of AsA and GSH in ROS scavenging in wheat [60] and potato [61]. A previous study had shown that drought priming induced the non-antioxidant defense system (AsA and GSH contents) to mitigate the harmful effects of ROS [62].…”
Section: The Positive Impact Of Drought-hardening On Nonenzymatic Antmentioning
confidence: 99%
“…This phenomenon suggests that osmotic stress by PEG served as an environmental signal factor for induction of the non-enzymatic antioxidant mechanism. Likewise, the application of PEG has increased AsA and GSH in tolerant genotypes of Chinese potato (Sahoo et al, 2020). On the other hand, application of PEG possessed a stimulatory effect on GSH content by 113.5%, whilst NaCl has provoked GSH by 32.0% compared to control.…”
Section: Induction Of Ascorbic Acid (Asa) and Reduced Glutathione (Gsh) Under Peg Applicationmentioning
confidence: 93%
“…The higher levels of H2O2 and MDA recorded under PEG treatment suggested that the extent of oxidative injury is much higher than defense mechanisms. According to Sahoo et al (2020), PEG mediated osmotic stress resulted in oxidative burst in Chinese potato genotypes as evident by accumulation of MDA as well as H2O2 in vitro. Such results is consistent with Lan et al (2020), who found high induction of MDA in PEG treatments, whilst stable MDA levels in NaCl-treated seedlings were recorded.…”
Section: Osmotic Stress Exaggerates the Production Of Hydrogen Peroxide And Malondialdehyde Contents More Than Salinity Stressmentioning
confidence: 99%